Sensitivity to the Demethylation Inhibitor Difenoconazole Among Baseline Populations of Various Penicillium spp. Causing Blue Mold of Apples and Pears - Madan Pandey; Clayton L. Haskell; Juliette D. Cowell; Achour Amiri (Journal of Fungi)
Difenoconazole (DIF), a demethylation inhibitor fungicide, was registered in 2016 for the control of postharvest diseases of pome fruits. In this study, 162 isolates from P. expansum (n = 31) and 13 other “non-expansum” Penicillium spp., i.e., P. solitum (n = 52), P. roqueforti (n = 32), P. commune (n = 15), P. paneum (n = 9), P. psychrosexuale (n = 8), P. crustosum (n = 5), P. carneum (n = 3), P. palitans (n = 2), along with one isolate each of P. citrinum, P. griseofulvum, P. raistrickii, P. ribium, and P. viridicatum, were collected from multiple packinghouses in the U.S. Pacific Northwest. In vitro sensitivity assays showed similar sensitivities of spores and mycelia across species with the mean EC50 values ranging from 0.01 for P. psychrosexuale (n = 8) to 1.33 μg mL−1 for P. palitans (n = 2), whereas the mean EC50s were 0.03, 0.12, 0.19, and 0.51 μg mL−1 for P. expansum (n = 31), P. paneum (n = 9), P. solitum (n = 52), and P. crustosum (n = 5), respectively. The recommended rate of DIF controlled P. expansum and P. roqueforti isolates but not all isolates of four other Penicillium spp. on Fuji apples after five months at 1.5 °C. The mixture of DIF + fludioxonil (FDL) (AcademyTM) controlled all the dual-sensitive isolates (DIFSFDLS) and DIF single-resistant (DIFR) isolates among the six species tested but not the FDLR and dual DIFRFDLR isolates. Notable polymorphism was detected in the CYP51 gene of the “non-expansum” species with four mutations located at four residues. Although the isolates analyzed in this study had not previously been exposed to DIF, the findings indicate variable sensitivity levels among the Penicillium spp.